Reliability of fitness trackers at different prices for measuring steps and heart rate: a pilot study - Kayla Ricchio; Penny Lyter-Antonneau; José M. Palao (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
The purpose of this pilot study was to assess the accuracy of steps and heart rate measurement of wrist fitness trackers at different prices. Four healthy college students voluntarily tested three wrist fitness bands and a sports watch (Xiaomi Mi Band, Fitbit Charge HRm, Fitbit Surge, and sports watch Polar M400). Subjects performed two sets of 10 series of 100 steps wearing the fitness trackers on an indoor track in two situations: walking and jogging. In the walking situation, the subjects wore a winter coat and gloves. The variables measured were the number of steps, the heart rate, and the level of error. The steps error percentage for all four devices was lower than 8%. The Fitbit Surge registered significantly more steps in the walking situation (p < 0.001). No significant differences were found in the steps measurements in the jogging situation (p = 0.138). In the jogging situation, significantly lower values in the heart rate measurements for the Xiaomi Mi Band, Fitbit Charger HR, and Fitbit Surge were found (p < 0.001). The results showed that the wearable fitness trackers were relatively accurate for tracking steps (on average, there was a level of error of 2-6%). The assessment of the steps was more accurate in the jogging situation (higher and faster arm swing) than in the walking situation, which involved wearing coats and gloves. The results showed that the wearable fitness trackers that were tested underestimate the heart rate with a level of error of approximately 6-11%. The step error was lower in the walking situation (less mobility of the devices). The price of the devices that were tested did not affect the accuracy of the steps and heart rate assessment. Further studies with a larger sample and more type of devices are needed to confirm these results.